COMPUTER SIMULATION METHODS FOR SOLVING PHYSICAL TASKS IN THE COURSE OF PHYSICS AT HIGH AND SECONDARY SCHOOLS - Babenko, M. (Journal of Information Technologies in Education (ITE), 2014)
The article considers issues of application of computer simulation methods in teaching process of the course of physics at high and secondary schools. It has been given an example of visualization of oscillation processes by different parameters of system based on SCM MATLAB that is conducive to deeper understanding of physical phenomena.